Guía didáctica “JUGANDO CON LAS TIC´S” para el aprendizaje de Ciencias Naturales en estudiantes de Quinto Año de Educación General Básica de la Unidad Educativa Isabel de Godín de la ciudad de Riobamba en el periodo junio-noviembre 2016” - Camacho Ledesma, Martha Beatriz (2017)
The research carried out on the basis of the application of ICT in the teaching process has as a fundamental objective to demonstrate whether the application of the Didactic Guide playing with ICT improves the learning in the students in the fifth year, the theoretical framework is supported in the operationalization of the hypothesis that covers the following topics: the methodology is of Pre-Experimental design, we used deductive and inductive methods each with their steps, respectively; The population was of 40 students. The alternative guidelines in the implementation of the technological resources allowed for an approach with the students through the use of educational social networks: the Facebook, collaborative resources, the ExamTime and the Google Drive, providing a significant step in the teaching with a constructivist approach. The contents developed showed significant improvements in knowledge, as well as with the application of the didactic guide, it was possible to observe a change of attitude in the students, since it works interactively; the hypotheses were tested using chi-square statistical analysis. From the research it is concluded that the implementation of the Didactic Guide playing with ICTS: Facebook, ExamTime and Google Drive enhance the learning of Natural Sciences in the fifth-year students and is recommended to teachers to assign these computer tools to facilitate the learning to students by transforming them into creative entities supported in the constructivist model with a view to create their own knowledge not only on the subject of Natural Sciences but also in other disciplines.